2021
DOI: 10.3390/cells10051229
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Myosin II Filaments during Wound Repair in Dividing Cells

Abstract: Wound repair of cell membranes is essential for cell survival. Myosin II contributes to wound pore closure by interacting with actin filaments in larger cells; however, its role in smaller cells is unclear. In this study, we observed wound repair in dividing cells for the first time. The cell membrane in the cleavage furrow, where myosin II localized, was wounded by laserporation. Upon wounding, actin transiently accumulated, and myosin II transiently disappeared from the wound site. Ca2+ influx from the exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…1B show a typical time course of fluorescence images of dividing cells expressing GFP-lifeact, a marker of actin filaments when the furrow membrane was wounded. Similar to our previous observations 25 , actin transiently accumulated between 2.5 and 26 s, with a peak at 10 s, after wounding.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…1B show a typical time course of fluorescence images of dividing cells expressing GFP-lifeact, a marker of actin filaments when the furrow membrane was wounded. Similar to our previous observations 25 , actin transiently accumulated between 2.5 and 26 s, with a peak at 10 s, after wounding.…”
Section: Resultssupporting
confidence: 91%
“…Cortexillin is a member of the alpha-actinin/spectrin superfamily, which localizes at the cleavage furrow and is required for its constriction [33][34][35][36] . We previously showed that cortexillin transiently disappears after wounding similar to myosin II 25 . Figure 2C shows the time course of furrow constriction in dividing cortexillin A and B double-null cells (Cortexillin A/B-null).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar to Xenopus oocytes, Dictyostelium cells, C. elegans hypodermal cells, and sea urchin coelomocytes have demonstrated myosin-independent wound closure mechanisms [ 12 , 14 , 78 , 87 ]. Wounded Dictyostelium cells did not exhibit additional myosin recruitment to the injury site and myosin null cells were able to repair wounds comparable to wild-type cells [ 12 , 87 ]. Likewise, coelomocytes treated with the kinase inhibitor KT5926 did not affect wound closure, indicating a myosin-independent wound closure mechanism [ 78 ].…”
Section: Actin Ring Translocationmentioning
confidence: 99%